Advanced Research in Naval Engineering (STEAM-H: Science, Technology, Engineering, Agriculture, Mathematics & Health,, 2018)
This multidisciplinary volume features invited contributions on mathematical applications in naval engineering. Seeking a more holistic approach that transcends current scientific boundaries, leading experts present interdisciplinary instruments and models on a broad range of topics. Each chapter places special emphasis on important methods, research directions, and applications of analysis within the field. Fundamental scientific and mathematical concepts are applied to topics such as the butterfly structure of the FFT, the acoustic impedance of pistons in a two-layer medium, deterministic batch trackers, spline equations, moving horizons estimation, membership games for planning sensor networks, statistical models of inertial sensors, random flight searches in bounded domains, the acoustics of a mixed porosity felt airfoil, and a novel aft boundary condition for a towed flexible cylinder. Carefully peer-reviewed and pedagogically presented for a broad readership, this volume is perfect for graduate and postdoctoral students interested in interdisciplinary research. Researchers in applied mathematics and sciences will find this book an important resource on the latest developments in the field. In keeping with the STEAM-H series, this volume hopes to inspire interdisciplinary understanding and collaboration.